Gestão por processos em organizações públicas: análise dos processos de aposentadoria e pensão civil na UFSM - Oliveira, Jefferson Menezes de (2015)
The objective of this study was to identify the main gaps in the administrative proceedings of retirement and civil pension managed by the Pro-Rectory of Personnel Management of the Federal University of Santa Maria (PROGEP/UFSM) in order to propose simplifications and improvements to the work routines. The guiding theoretical framework of the study included the lines: (i) process management, (ii) process management in public administration and (iii) Social Security of the federal public servant: Retirement and civil pension. In addition, was built an analysis of the "State of the Art" (iv). With a qualitative approach, this case study uses different sources of evidence: documentation, records in archives, the semi-structured interviews, direct observation and participative observation. In compliance with the first specific objective of the study, an analysis of the retirement and civil pension proceedings made by PROGEP/UFSM was held, followed by the mapping of them in the form of diagrams of processes, and the identification of actors involved from the construction of matrices of responsibilities. Following, on the second and third specific objectives, in order to identify the most appropriate opportunities to improve the work routines, semi-structured interviews were conducted with those involved in the retirement and civil pensions proceedings conducted in the institution, including end users of services and employees. Finally, in the fourth specific objective the triangulation of data allowed to identify the main opportunities to improve the processes for retirement and civil pension, , emphasizing the procedural delay, outbreaks of rework and bottlenecks, insufficient focus on the user and inadequate working conditions. Thus, proposals have been made for simplification and improvements in the processes in order to solve these gaps. It was found that the proposals of greater amplitude may have more effective results in the long term, because it best fit on the available literature related to the management by processes. However, the realization of more complex changes will depend on ability by the PROGEP/UFSM manager in order to break with the functional paradigm.